Anti-cyclic citrullinated peptide antibodies and rheumatoid factor in leprosy patients with articular involvement - Ribeiro,S.L.E. (2008)
The objective of the present research was to evaluate the usefulness of anti-cyclic citrullinated peptide (anti-CCP) antibodies and the IgM rheumatoid factor (IgM RF) test for the differential diagnosis of leprosy with articular involvement and rheumatoid arthritis (RA). Anti-CCP antibodies and IgM RF were measured in the sera of 158 leprosy patients (76 with and 82 without articular involvement), 69 RA patients and 89 healthy controls. Leprosy diagnosis was performed according to Ridley and Jopling classification criteria and clinical and demographic characteristics of leprosy patients were collected by a standard questionnaire. Leprosy patients with any concomitant rheumatic disease were excluded. Serum samples were obtained from all participants and frozen at _20°C. Measurement of anti-CCP antibodies and IgM RF were performed by ELISA, using a commercial second-generation kit, and the latex agglutination test, respectively. Anti-CCP antibodies and IgM RF were detected in low frequencies (2.6 and 1.3%, respectively) in leprosy patients and were not associated with articular involvement. Among healthy individuals both anti-CCP antibodies and IgM RF were each detected in 3.4% of the subjects. In contrast, in the RA group, anti-CCP antibodies were present in 81.2% and IgM RF in 62.3%. In the present study, both anti-CCP antibodies and IgM RF showed good positive predictive value for RA, helping to discriminate between RA and leprosy patients with articular involvement. However, anti-CCP antibodies were more specific for RA diagnosis in the population under study.